STUDI PELEPASAN KURKUMIN MENGGUNAKAN MEMBRAN KITOSAN-PEKTIN DENGAN PENAMBAHAN ASAM LAURAT SEBAGAI EMULSIFIER - , NINDYA HERDIANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Curcumine release from chitosan-pectin film using lauric acid as emulsifier had been studied. The aim of this study was to determine the optimum condition of curcumin release using some variations, such as curcumine consentrations, lauric acid concentrations, ethanol concentrations and pH of solvent. Film was prepared by mixing pectin with aquades, then adding chitosan and acetic acid 1%, then adding lauric acid and curcumine until it was mixed completely. The products were characterized by spectrometer IR. Curcumin release had been done by immersing film in a phospate buffer-ethanol solution for 6 hours. The concentration of curcumine release was measured by Spectrofotometer UV-Vis. Curcumine release kinetics were analyzed by zeroorder model, first-order model, Higuchi model and Korsmeyer-Peppas model. The ressult showed that the most suitable kinetics model of this experiment was Korsmeyer-Peppas. The optimum condition of curcumin release had been given by film which had 200ppm curcumin and 5mg lauric acid. The most optimum solvent was phosphate buffer:ethanol 80:20 pH7. The release rate was 0,31 cm-1.